Hubungan Antara Intensitas Bermain Game Online Dengan Kecerdasan Emosional Pada Siswa SMP Negeri 16 Singkawang - Kelvin Hilmawan; Insan Suwanto; Dewi Mariana (SABER : Jurnal Teknik Informatika, Sains dan Ilmu Komunikasi, 2025)
This study aims to determine: (1) the intensity of playing online games among students at SMP Negeri 16 Singkawang, (2) the level of emotional intelligence among students at SMP Negeri 16 Singkawang, and (3) the relationship between the intensity of playing online games and emotional intelligence among students at SMP Negeri 16 Singkawang. This research uses a quantitative approach with a causal associative research design. The population of this study consisted of students from classes VII D, VIII D, and IX D at SMP Negeri 16 Singkawang, totaling 105 students, with a research sample of 105 students selected using a total sampling technique. Data analysis to determine the intensity of playing online games and emotional intelligence among students was carried out using descriptive statistical analysis. Meanwhile, to analyze the relationship between the intensity of playing online games and emotional intelligence, the Pearson product-moment correlation technique was used. The results of the data analysis show that: (1) the level of online game playing intensity among students at SMP Negeri 16 Singkawang falls into the low category (36.87), (2) the level of emotional intelligence among students is in the high category (112.8), and (3) there is no significant relationship between the intensity of playing online games and emotional intelligence among students, with an R value of -0.124. Therefore, it can be concluded that there is no relationship between the intensity of playing online games and the emotional intelligence of students at SMP Negeri 16 Singkawang. In conclusion, the higher the intensity of playing online games, the lower the emotional intelligence of students.